The Effect of Demographics and Marketing Mix on Purchasing Decisions at Modern and Traditional Coffee Shops in Makassar - Bhirawidha, Arhab (Politeknik Siber Cerdika Internasional, 2025)
The rapid growth of the coffee shop industry has led to an increased interest in understanding consumer behavior, particularly in urban areas like Makassar. This study aims to analyze the influence of demographic factors and the marketing mix on purchasing decisions at modern and traditional coffee shops in Makassar. Specifically, it examines the role of age, gender, monthly consumption, product, price, place, and promotion in shaping consumer preferences.The research adopts a quantitative approach, employing logistic regression to assess the relationship between demographic and marketing mix variables (independent variables) and purchasing decisions (dependent variable). Data were collected through questionnaires distributed to 184 respondents who frequently visit coffee shops in Makassar. Prior to analysis, the validity and reliability of the research instruments were thoroughly tested to ensure data accuracy. The findings reveal that demographic factors, including age, gender, and monthly consumption, significantly influence purchasing decisions. Younger consumers tend to prefer modern coffee shops, while those with higher consumption levels are more inclined to choose traditional coffee shops. Interestingly, the marketing mix variables—product, price, place, and promotion—do not show a significant impact on purchasing decisions, diverging from the results of some previous studies. These results have important implications for coffee shop managers in tailoring their strategies to target specific consumer demographics more effectively. Furthermore, the study underscores the need for a deeper exploration of other potential factors beyond the marketing mix that could influence purchasing decisions in the coffee shop industry.